2023
DOI: 10.5530/pj.2022.14.169
|View full text |Cite
|
Sign up to set email alerts
|

Nano Transdermal Delivery Potential of Fucoidan from Sargassum sp. (Brown Algae) as Chemoprevention Agent for Breast Cancer Treatment

Abstract: Conventional chemotherapy substances are associated with mild to severe side effects that affect both healthy and cancer cells. It is presumed to improve therapeutic efficacy in coexistence reducing chemotherapy's side effects. Fucoidan is an anticancer bioactive compound derived from Sargassum sp. that has low cytotoxic activity. The purpose of this study was to explore the effectiveness of anticancer activities of fucoidan from Sargassum sp. against breast cancer then analyze the suitability of nano transder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…These conclusions were mainly obtained by in vitro assays, more in vivo studies, especially the patient derived xenograft models, are needed to confirm the regulatory mechanism of HANR/HK2 axis, which would enhance the robustness and translational relevance of the study. Recent study reported that nano transdermal delivery of fucoidan, an anticancer bioactive compound derived from Sargassum sp., showed local effects on the site of breast cancer cells using fucoidan nanoparticle polymer [ 41 ]. Secondary metabolites in Algae Kappaphycus alvarezii shows potential anti-cancer potency in breast cancer [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…These conclusions were mainly obtained by in vitro assays, more in vivo studies, especially the patient derived xenograft models, are needed to confirm the regulatory mechanism of HANR/HK2 axis, which would enhance the robustness and translational relevance of the study. Recent study reported that nano transdermal delivery of fucoidan, an anticancer bioactive compound derived from Sargassum sp., showed local effects on the site of breast cancer cells using fucoidan nanoparticle polymer [ 41 ]. Secondary metabolites in Algae Kappaphycus alvarezii shows potential anti-cancer potency in breast cancer [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on data from the Global Cancer Observatory (2020), breast cancer cases have a high prevalence in Indonesia (Ng et al, 2023). The incidence of new cases of breast cancer in Indonesia reached 68,858 cases, and the death rate was more than 22 thousand people in 2020 (Hamami et al, 2022). This makes breast cancer one of the first causes of death due to cancer in Indonesia.…”
Section: Introductionmentioning
confidence: 99%